The use of photodynamic therapy in combined treatment of actinic keratosis - Małkińska, Katarzyna; Bartosińska, Joanna; Kwaśny, Mirosław; Krasowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2020)
Actinic keratosis, a type of squamous cell carcinoma in situ, is characterised by hyperkeratotic focal lesions formed on the ultraviolet-damaged skin. Usually, there are a few to several so foci of actinic keratosis, and less often a single lesion is present. The treatment depends on the number, size, duration, and location of lesions. This study discusses some options of combined treatment of actinic keratosis and the possible risk of cancer associated with the use of photodynamic therapy in combination with laser therapy, topical medications (imiquimod, 5-fluorouracil, diclofenac, topical retinoids, ingenol mebutate, calcipotriol), and microneedling. Combined treatment is worth considering in cases of numerous hyperkeratotic foci, particularly in difficult-to-treat locations. Effective photoprotection is essential for all persons with actinic keratosis.